Profile of Social Cohesion Ability of SDN 15 Pamatang Panjang Students, Sijunjung Regency - Fadil Maiseptian; Erna Dewita; Mezia Kemala Sari; Dini Susanti; Nurhamsi Deswila (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The importance of developing students' social cohesion attitudes cannot be separated from the heterogeneous conditions of Indonesian society. Cultural diversity, ethnicity, language, race, religion, and customs can cause differences in understanding and perspective on an object so this has the potential to cause divisions between members of the community. The purpose of this study was to determine the social cohesion ability of elementary school students from the aspect of belonging, mutual openness, recognition/award, and participation/goal. This type of research uses a quantitative descriptive approach. The data collection technique used a social cohesion questionnaire with a total sampling of 53 people as research subjects. The data analysis technique used the percentage formula P=f/N x 100%. The condition of students' social cohesion from the aspect of belonging, mutual openness, recognition/award, and participation/goal is in the high category. Therefore, students need to develop themselves through various study group activities, to be able to take valuable lessons for their future. Student study groups will help hone various student abilities, including a sense of belonging, mutual openness, recognition/awards, and participation goal.